2015
DOI: 10.5562/cca2479
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Kinetic Investigation of Comparative Ligand Effect on Cysteine Iron Redox Reaction

Abstract: Abstract. Transition metal ions in their free state bring unwanted biological oxidations generating oxidative stress. The ligand modulated redox potential can be indispensable in prevention of such oxidative stress by blocking the redundant bio-redox reactions. In this study we investigated the comparative ligand effect on the thermo-kinetic aspects of biologically important cysteine iron (III) redox reaction using spectrophotometric and potentiometric methods. The results were corroborated with the complexati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The formal potential of transition metals redox couples can be modulated through the complexation with a suitable ligand. , Particularly, it has been reported that the redox potential of the Fe­(III)/Fe­(II) couple is shifted to more negative values upon complexation with ions such as citrate, chloride, oxalate, or ethylenediaminetetraacetic acid (EDTA). Herein, we studied the effect of complexation of Fe­(II) with citrate and chloride ions in the AuNPs synthesis. Thus, experiments in the presence of different citrate concentration (0.5, 0.75, and 1 mM) were performed at 40 °C for Au­(III):Fe­(II) molar ratio of 1:3 and for concentrations of PSS and Au­(III) of 0.5 mg/mL and 0.5 mM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The formal potential of transition metals redox couples can be modulated through the complexation with a suitable ligand. , Particularly, it has been reported that the redox potential of the Fe­(III)/Fe­(II) couple is shifted to more negative values upon complexation with ions such as citrate, chloride, oxalate, or ethylenediaminetetraacetic acid (EDTA). Herein, we studied the effect of complexation of Fe­(II) with citrate and chloride ions in the AuNPs synthesis. Thus, experiments in the presence of different citrate concentration (0.5, 0.75, and 1 mM) were performed at 40 °C for Au­(III):Fe­(II) molar ratio of 1:3 and for concentrations of PSS and Au­(III) of 0.5 mg/mL and 0.5 mM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(3)] and makes Fe(III) cysteine redox reaction spontaneous. Potentiometric titration of Fe(III) with cysteine [20] displayed the potential jump at the equivalence point only in presence of the ligand and ca 50°C. Potential change in the vicinity of the inflection point was found to be proportional to stability of Fe(II) complex with the selected ligands (Fig.…”
Section: 3mentioning
confidence: 99%
“…[9][10][11] These compounds can act as potential ligands with good binding interactions towards metal ions, [12][13] forming complexes that modify the redox behavior of metals [14] as reported for Fe II complexation by ligands. [3,4,[15][16][17] The impact of different organic ligands can be rationalized in terms of the complexation effect on the reduction potential of Fe III /Fe II redox couple, [14,18,19] Depending upon relative stabilization of the two oxidation states in transition metal redox couple, different ligands tune the formal redox potential of the Fe III -Fe II couple to a range of values. Modulating the redox potential of environmentally widespread Fe II ions by complexation with naturally occurring organic compounds can be interesting towards natural attenuation of contaminants under environmental conditions, [5][6][7][8] In continuation of our interest in using coordination compounds for synthetic and environmental applications, [20][21][22][23][24][25] this work presents the use of Fe II -complexes with prevalent compounds as ligands for waste water treatment under environmental conditions (aerobic, 20°C, pH 6-7).…”
Section: Introductionmentioning
confidence: 99%